THE PRODUCTIVITY DAMS OF KACANG, BLINGON AND ETAWA CROSS IN SEMI INTESIF GOAT FARMING: PRODUKTIVITAS INDUK KAMBING KACANG, BLINGON DAN PERANAKAN ETAWA YANG DIPELIHARA SECARA SEMIINTENSIF - Tampubolon, Yusni Khairani (Universitas Boyolali, 2022)
This study aims to determine the productivity of Kacang, Peranakan Etawa (PE) and Blingon dam goats reared together with a semi-intensive system. Seven Kacang dams, seven PE dams and seven Blingon dams were kept in cages to mate with buck in the same breed. After birth, the dams and kids were moved to individual cages. At the kids a month old, dams and kids were transferred to the mating cage. When they reach 90 days of weaning, the cubs are separated from dams. Data collected were kidding interval (KI), birth weight (BW), weaning weight (WW), daily body weight gain (BWG), litter size (LS), pre-weaning mortality, reproduction rate of dam and dam’s productivity . Data were analyzed using One way – ANOVA. The results showed that KI fro, Kacang had the shortest (P<0.01) than the PE and Blingon was 229.14±35.39 day. BW from PE goats had the largest (P<0.05) than Kacang and Blingon was 3.26±0.72 kg. WW from PE dams had the highest (P<0.01) was 10.29±0.88 kg. BWG from PE goats had the highest (P<0.01) than Kacang and Blingon was 0.08±0.01 kg/day. Reproduction rate of dam of Kacang and Blingon had a higher (P<0.01) than PE were 1.82±0.23 and 1.65±0.25 head/year. There was no significant diiferent LS and dam’s productivity between Kacang, PE and Blingon. It is concluded that Kacang dams had better reproduction rates and kiddingintervals than PE and Blingon goats. Keywords : Blingon, Kacang, Peranakan Etawa, Goat Productivity